Artisanats Antiques D’Italie Et De Gaule 2009
DOI: 10.4000/books.pcjb.4248
|View full text |Cite
|
Sign up to set email alerts
|

La fabrication du bleu égyptien à Cumes

Abstract: Le bleu égyptien, qui porte ausi les noms de « bleu d'Alexandrie», « bleu Vestorien », « bleu de Pouzzoles », « bleu Pompéien », caeruleum ou encore hsbd iryt en égyptien hiéroglyphique, terme qui signifie littéralement « lapis-lazuli fabriqué », trouve son origine en Égypte. Cette couleur est le premier pigment de synthèse créé par les Égyptiens durant la IV e dynastie (2613-2494 avant J.-C.) 1 pour pallier la carence en minéraux naturels tels que le lapis-lazuli, pierre semiprécieuse, que sa rareté réservait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Likewise, the addition of an alkaline flux in the form of soda-rich or mixed-alkaline plant ash was reinforced due to the detection of mainly sulphate and phosphate salts of sodium and potassium as well as magnesium and calcium. Such corresponding trace constituents in Roman Imperial and Early Medieval Egyptian blue provide sound scientific evidence of a continuous production and trade monopoly in the Gulf of Pozzuoli surviving from the first centuries A.D. up to the politically turbulent period after the fall of the Western Roman Empire, this in line with statements of the antique Roman writers Vitruvius 3 and Pliny the Elder 4 and recent archaeological finds in the cities of Cumae and Liternum 6 8 .…”
Section: Conclusion: Evidences For the Provenance Of The Raw Material...supporting
confidence: 70%
“…Likewise, the addition of an alkaline flux in the form of soda-rich or mixed-alkaline plant ash was reinforced due to the detection of mainly sulphate and phosphate salts of sodium and potassium as well as magnesium and calcium. Such corresponding trace constituents in Roman Imperial and Early Medieval Egyptian blue provide sound scientific evidence of a continuous production and trade monopoly in the Gulf of Pozzuoli surviving from the first centuries A.D. up to the politically turbulent period after the fall of the Western Roman Empire, this in line with statements of the antique Roman writers Vitruvius 3 and Pliny the Elder 4 and recent archaeological finds in the cities of Cumae and Liternum 6 8 .…”
Section: Conclusion: Evidences For the Provenance Of The Raw Material...supporting
confidence: 70%
“…The typological study of these materials by Caputo and Cavassa 16 and Cavassa et al 17 identified two types of containers: a globular/closed one with height of~30-40 cm and bottom/top diameter of~20 cm [type 1, Fig. 1(b)] and a cylindrical/open form with height from 40 to 50 cm and diameter of~30 cm [type 2, Fig.…”
mentioning
confidence: 99%
“…It was able to detect elements which reveal the production period. In fact, most of the pigments have been used since the Roman period: the blue pigment is an egyptian blue whose production is documented in Cuma [21]. The mortar radiocarbon dating is a reliable technique especially at the archaeological sites where there are scarce materials to date.…”
Section: Discussionmentioning
confidence: 99%